Dinamika Populasi Bakteri dalam Air dan Sedimen Tambak pada Pemantapan Budidaya Udang Vaname Ekstensif Plus Melalui Pergiliran Pakan - Markus Mangampa (Berkala Perikanan Terubuk, 2015)
Dynamics of populations of bacteria isolated from water and sediments oil brachkis water pond vannamei shrimp (Litopenaeus vannamei) extensive plus the feeding regime. The research was conducted at the research instalation of the Research Institute for Coastal Aquaculture (Balitbang BAP), in Marana, Maros Regency. This research was aimed to study at the population growth of bacteria in the water and sediment in the brachkis water pond throuh feeding regime. The tretment was applied with gradual reduction of protein feed for culture period.Six ponds each sized of 2500 m2 were used in this research with vannamei juvenile (PL-25) with stocking density 8ind/m2(extensive plusculture). The treatments were tested in thi sactivity is the rotation period of high protein feed (38%) to moderate protein (34%), and low rotein (30%), with the composition of the treatment: A=feeding regime of high protein feed to protein being at the first-week 1 (low protein); B=feeding regime of high protein feed to protein being at the third week (medium protein); C=feeding regime of high protein feed to protein being at the 5th-week (high protein). Each treatment was arranged in two replications and reared for 75 days.The results obtained range of bacteria Vibrio sp population in pond water treatment A(2,59x102-1,99x102) cfu/mL; B(2,55x102-2,23x102) cfu/mL; and C (4,22x102-0,90x102) cfu/mLwitha total bacteria (TPC) in the water pond A (3,23x104-3,03x104) cfu/mL; B (3,55x104-1,88x104) cfu/mL; and C (2,45x104-2,14x102) cfu/mL. Total Vibrio spon sediment pond is A(3,75x103-1,82x104) cfu/g; B (4,17x103-6,22x104) cfu/g; and C (2,94x104-1,47x103) cfu/g with a total bacteria (TPC) in the sediment pond is A (2,59x106-2,62x105) cfu/g; B (2,07x106-3,56x106) cfu/g; and C (2,76x106-3,09x106) cfu/g for 75 days of culture period. Water quality parameters showed similar variation in both treatment, except amonia and total organik matter.